2019
DOI: 10.1016/j.respol.2018.12.004
|View full text |Cite|
|
Sign up to set email alerts
|

The geography of venture capital and entrepreneurial ventures’ demand for external equity

Abstract: In this paper, we study how the geography of venture capital (VC) and the location of entrepreneurial ventures affect the propensity of the latter to seek external equity financing. We analyse a sample of 533 European high-tech entrepreneurial ventures and examine their external equity-seeking behaviour in the 1984-2009 period. We find that ventures are more likely to seek external equity when the local availability of VC is higher, whereas the level of competition of the local VC market plays a negligible rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 75 publications
3
34
0
Order By: Relevance
“…Previous studies have shown that accessing external finance from traditional channels is challenging for firms located in peripheral areas (i.e. far from great metropolitan areas where VC investors are concentrated, Chen et al, 2010;Colombo et al, 2019) and for minority entrepreneurs (e.g. female and ethnic entrepreneurs, Verheul & Thurik, 2001).…”
Section: Equity Crowdfunding and Financial Inclusionmentioning
confidence: 99%
“…Previous studies have shown that accessing external finance from traditional channels is challenging for firms located in peripheral areas (i.e. far from great metropolitan areas where VC investors are concentrated, Chen et al, 2010;Colombo et al, 2019) and for minority entrepreneurs (e.g. female and ethnic entrepreneurs, Verheul & Thurik, 2001).…”
Section: Equity Crowdfunding and Financial Inclusionmentioning
confidence: 99%
“…Recent accounts, however, do not support this argument: peripheral underdeveloped regions may suffer from a lack of infrastructure, R&D and innovation intensity, and appropriate quality of entrepreneurial human capital (Munari and Toschi, 2015). These characteristics result in smaller founding rates, lower quality YICs and thus a lower demand for risk capital (Bernstein et al, 2017;Colombo et al, 2019;Gompers et al, 2016).…”
Section: Location/colocationmentioning
confidence: 99%
“…The literature indicates that PVCs and their investments exhibit a considerable level of spatial concentration in financial centers and hightech regions (Chen et al, 2010;Colombo et al, 2019). To compensate for potential equity gaps in economically lagging areas, governments have often implemented local GVC programs to foster regional development (Bertoni et al, 2017;Bertoni and Tykvová, 2015;Kovner and Lerner, 2015;Lerner, 1999Lerner, , 2002.…”
Section: Location/colocationmentioning
confidence: 99%
“…These agency concerns are geographical because BAs invest locally to allow close monitoring of their investments (Shane and Cable, 2002). Distance 'amplifies information asymmetries' and creates uncertainty because of the unfamiliarity of the context within which a venture is embedded (Colombo et al, 2019(Colombo et al, , p. 1152). To cope with these problems investors' often look to their own personal networks.…”
Section: Informational and Agency Issuesmentioning
confidence: 99%